3DCP for complex sites: robotic fabrication of custom-fit slabs in irregular pontoons - Ribeiro, João (2024)
This paper presents a case study on the use of 3DCP to qualify rocky pontoons with spaces for recreational use—namely sitting areas, circulation trails and fishing activities—and biodiversity protection—providing habitat and refuge for native marine species—with a focus on the challenges and opportunities associated with 3DCP prefabrication for such a complex topographical context. We first discuss the benefits and disadvantages of 3DCP over traditional methods for retrofitting strategies with the support of state-of-the-art literature review. We then present a methodology for an experimental case study, organized in three stages: (1) a photogrammetric survey and digital reconstruction of the site´s rocky landscape, (2) the creation of a tool to generate and optimize custom-fit slabs based on their location on site, intended use and role in the protection of the natural ecosystem, and (3) the robotic fabrication of these slabs through 3DCP. Finally, we present our key findings, revealing that 3DCP offers a viable and more efficient alternative for appropriating and revitalizing sites with a disorderly and highly complex topography.